Search for a CP-odd Higgs boson decaying into a heavy CP-even Higgs boson and a Z boson in the ℓ+ℓ−t¯t and ν¯νb¯b final states using 140 fb−1 of data collected with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2024)
A search for a heavy CP-odd Higgs boson, A, decaying into a Z boson and a heavy CP-even Higgs boson, H, is presented. It uses the full LHC Run 2 dataset of pp collisions at √s = 13 TeV collected with the ATLAS detector, corresponding to an integrated luminosity of 140 fb−1. The search for A → ZH is performed in the ℓ+ℓ−t¯t and ν ¯νb¯b final states and surpasses the reach of previous searches in different final states in the region with mH > 350 GeV and mA > 800 GeV. No significant deviation from the Standard Model expectation is found. Upper limits are placed on the production cross-section times the decay branching ratios. Limits with less model dependence are also presented as functions of the reconstructed m(t¯t) and m(b¯b) distributions in the ℓ+ℓ−t¯t and ν ¯νb¯b channels, respectively. In addition, the results are interpreted in the context of two-Higgs-doublet models.
Im Text ist "+" "-" und "-1" hochgestellt
The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 25.10.2024